2018
DOI: 10.1186/s12915-018-0608-2
|View full text |Cite
|
Sign up to set email alerts
|

Migration through a small pore disrupts inactive chromatin organization in neutrophil-like cells

Abstract: BackgroundMammalian cells are flexible and can rapidly change shape when they contract, adhere, or migrate. The nucleus must be stiff enough to withstand cytoskeletal forces, but flexible enough to remodel as the cell changes shape. This is particularly important for cells migrating through confined spaces, where the nuclear shape must change in order to fit through a constriction. This occurs many times in the life cycle of a neutrophil, which must protect its chromatin from damage and disruption associated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 100 publications
6
40
2
Order By: Relevance
“…Bottom-5 cells exhibit a loss in the strongest B-B interactions and an overall increase in interactions between the strongest B and strongest A compartments. This phenomenon has been previously reported in neutrophils after passage through small pores, suggesting it may be a general feature of confined migration genomic structural changes (Jacobson et al, 2018). This change in interaction frequency correlates with changes in gene expression.…”
Section: Inter-compartment Interactions Increase After Constricted MIsupporting
confidence: 77%
See 2 more Smart Citations
“…Bottom-5 cells exhibit a loss in the strongest B-B interactions and an overall increase in interactions between the strongest B and strongest A compartments. This phenomenon has been previously reported in neutrophils after passage through small pores, suggesting it may be a general feature of confined migration genomic structural changes (Jacobson et al, 2018). This change in interaction frequency correlates with changes in gene expression.…”
Section: Inter-compartment Interactions Increase After Constricted MIsupporting
confidence: 77%
“…This suggests that confined migration itself can induce some of the changes we observe. As passage through a constriction physically moves the chromosomal regions in the nucleus, certain interactions, such as the strongest B-B interactions in our data, may be pulled apart as suggested by chromatin stretching previously described (Irianto et al, 2017b) and loss of B-B interaction strength with confined migration observed in neutrophils (Jacobson et al, 2018). Meanwhile, loci previously more distant are given an opportunity to associate and may form new aggregates through phase separation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In order to investigate transcriptional responses to TNF-α, the promyelocytic cell line HL-60/S4 was differentiated into a granulocytic form by treatment with ATRA for 96 hours, as described previously [36]. Both undifferentiated (promyelocytic) and differentiated (granulocytic) cells were treated with 16ng/mL TNF-α in calcium supplemented media for two hours.…”
Section: Resultsmentioning
confidence: 99%
“…As required, cells were differentiated into a granulocytic phenotype with 1 µM all trans retinoic acid (ATRA) dissolved in ethanol (Sigma Aldrich) for four days as previously described ( [30,36,72]). Cells were centrifuged (200xg, 5 min, room temp.)…”
Section: Cell Culturementioning
confidence: 99%